2011
DOI: 10.1177/0883073811420495
|View full text |Cite
|
Sign up to set email alerts
|

The Demographic, Clinical, and Magnetic Resonance Imaging (MRI) Features of Transverse Myelitis in Children

Abstract: The authors collected demographic, clinical, and neuroimaging data prospectively on 38 children with transverse myelitis. One child died during the illness. The female:male ratio was 1.2:1 for children under age 10 years and 2.6:1 over age 10 years. Twenty-eight (74%) reported a prodromal event. Twenty-two patients (58%) had longitudinally extensive transverse myelitis, 9 (24%) had focal lesions, and 5 (13%) had both. Twenty of 33 with brain imaging (61%) had brain lesions; 7 fulfilled McDonald criteria for di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
93
4
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(104 citation statements)
references
References 40 publications
6
93
4
1
Order By: Relevance
“…Children with ADEM had the longest hospital stays, whereas children with ON had the shortest hospital stays ( Severe deficits in $1 feature of vision, motor, bladder and bowel function, or cognition were detected at ADS onset in 133 (47.0%) of 283 children, whereas 51 (18.0%) children had $1 moderate deficit, and 79 (27.9%) children had at least 1 mild deficit (Supplemental Fig 3A). Twenty (7.1%) children had a normal examination at study enrollment (days from onset, median [range]: 9 [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]); all had at least 1 deficit at onset verified according to records review of their presenting examination.…”
Section: Clinical Severitymentioning
confidence: 99%
See 1 more Smart Citation
“…Children with ADEM had the longest hospital stays, whereas children with ON had the shortest hospital stays ( Severe deficits in $1 feature of vision, motor, bladder and bowel function, or cognition were detected at ADS onset in 133 (47.0%) of 283 children, whereas 51 (18.0%) children had $1 moderate deficit, and 79 (27.9%) children had at least 1 mild deficit (Supplemental Fig 3A). Twenty (7.1%) children had a normal examination at study enrollment (days from onset, median [range]: 9 [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]); all had at least 1 deficit at onset verified according to records review of their presenting examination.…”
Section: Clinical Severitymentioning
confidence: 99%
“…We previously described 38 children with TM (none included in the present analysis); 6 (16%) experienced residual motor impairment and 8 (22%) experienced residual bladder impairment. 15 In a European study of 95 children with TM, 28 (30%) experienced a poor outcome (defined as Expanded Disability Status Scale score $4). 16 Of 47 children reported from the Johns Hopkins Myelitis Center, 17 ten (21%) patients required a walker or other support and 22 (50%) of 44 required bladder catheterization.…”
Section: Clinical Severitymentioning
confidence: 99%
“…8 Although males are more likely to present with ATM (male:female ratio 1.1-1.6:1), a female preponderance is seen among teenagers in regions at high risk for MS and NMO (United States, Canada, Europe, and parts of Australia). [6][7][8][9][10][11][12] A bimodal age distribution is observed in children under 5 and older than 10 years of age. 3,8,9,[11][12][13] There is no difference in ethnicity prevalence.…”
mentioning
confidence: 99%
“…In other my- elopathies, particularly inflammatory myelopathies in children, younger age at onset and the presence of sphincter involvement were associated with a poorer clinical prognosis. 16,17 Imaging studies revealed that T1 hyposignal and extensive lesions could be MR imaging signs predictive of poorer outcome. In our study, we did not observe any clinical or MR imaging criteria able to distinguish recurrence or more severe ASIA scale apart from younger age, though not significant, suggesting that these factors are less important in hematomyelia in contrast to inflammatory myelopathies.…”
Section: Open Arrow) On Angiography the Avm (Open Arrow) Is Fed By mentioning
confidence: 99%